PENGARUH VARIASI HEAT ABSORBER PLATE TERHADAP PERFORMANCE SOLAR DRYER KEMIRI - Anggara, Mietra; Firda Utami, Silvia (Jurnal TAMBORA, 2020)
Indonesia one of the plants that leaves and seeds grow has many useful benefits for human life, namely candlenut. The post-harvest handling of candlenut at the farm level it is generally still done traditionally where candlenut is drying on the floor or by direct exposure to solar radiation. They need approximately 7-9 days to get the appropriate drying results. Candlenut drying is influenced by the intensity of solar radiation on temperature and drying time according to the required hazelnut content. the dry hazelnut can use solar radiation power that is solar dryer. Absorbent plate is one component that is very important because it functions to absorb the intensity of solar radiation and convert it into heat energy and move it to the workpiece (candlenut) above it. In this study, testing was done on variations of the absorbent plates of zinc, aluminum and iron as well as variations in the thickness of the absorbent plates. Data collection starts at 09:00 until 15:00 WITA in sunny weather conditions. The results showed that the aluminum absorbent plate with a thickness of 0.04 mm was more effective and efficient in drying the candlenut to increase the productivity of the candlenut. The highest absorbent plate temperature and drying time were found on the aluminum absorbent plate with a thickness of 0.4 mm that is 72.36 oC and a drying time of 6 hours and meets the standard of moisture content of candlenut solution, which is 5.3%.